Expression of Tac antigen component of bovine interleukin-2 receptor in different leukocyte populations infected with Theileria parva or Theileria annulata. - Dobbelaere, D A (1990)
The Tac antigen component of the bovine interleukin-2 receptor was expressed as a Cro-beta-galactosidase fusion protein in Escherichia coli and used to raise antibodies in rabbits. These antibodies were used for flow cytofluorimetric analysis to investigate the expression of Tac antigen in a variety of Theileria parva-infected cell lines and also in three Theileria annulata-infected cell lines. Cells expressing Tac antigen on their surface were found in all T. parva-infected cell lines tested whether these were of T- or B-cell origin. T cells expressing Tac antigen could be CD4- CD8-, CD4+ CD8-, CD4- CD8+, or CD4+ CD8+. Tac antigen expression was observed both in cultures which had been maintained in the laboratory for several years and in transformed cell lines which had recently been established by infection of lymphocytes in vitro with T. parva. Northern (RNA) blot analysis demonstrated Tac antigen transcripts in RNA isolated from all T. parva-infected cell lines. Three T. annulata-infected cell lines which were not of T-cell origin were also tested. Two of them expressed Tac antigen on their surface. Abundant Tac antigen mRNA was detected in these T. annulata-infected cell lines, but only trace amounts were demonstrated in the third cell line, which contained very few Tac antigen-expressing cells. In all cell lines tested, whether cloned or uncloned, a proportion of the cells did not express detectable levels of Tac antigen on their surface. This was also the case for a number of other leukocyte surface markers. In addition, we showed that the interleukin-2 receptors were biologically functional, because addition of recombinant interleukin-2 to cultures stimulated cell proliferation. Recombinant interleukin-2 treatment also resulted in increased amounts of steady-state Tac antigen mRNA. The relevance of interleukin-2 receptor expression on Theileria-infected cells is discussed.